2019
DOI: 10.3390/computers8040079
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Crypto-Ransomware Using a Pre-Encryption Detection Algorithm

Abstract: Ransomware is a relatively new type of intrusion attack, and is made with the objective of extorting a ransom from its victim. There are several types of ransomware attacks, but the present paper focuses only upon the crypto-ransomware, because it makes data unrecoverable once the victim’s files have been encrypted. Therefore, in this research, it was proposed that machine learning is used to detect crypto-ransomware before it starts its encryption function, or at the pre-encryption stage. Successful detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…e algorithm can effectively reduce the false alarm rate and network delay, but in real-time detection, the detection efficiency of the algorithm needs to be improved. In [21], a preencryption detection algorithm is proposed to detect encrypted ransomware. Compared with some algorithms based on machine learning, it is found that the proposed preencryption algorithm has better performance and a lower false alarm rate.…”
Section: Related Workmentioning
confidence: 99%
“…e algorithm can effectively reduce the false alarm rate and network delay, but in real-time detection, the detection efficiency of the algorithm needs to be improved. In [21], a preencryption detection algorithm is proposed to detect encrypted ransomware. Compared with some algorithms based on machine learning, it is found that the proposed preencryption algorithm has better performance and a lower false alarm rate.…”
Section: Related Workmentioning
confidence: 99%
“…Developing a software from scratch is comparable to reinventing the wheel by many, hence solutions are offered to secure existing software systems. Some to name are Component-Based Software Engineering (CBSE), use of authentication schemes, systematic frameworks, graphical authentication models for mobile devices and applications [8], specialized attack detection techniques [9], etc. CBSE helps in minimizing the efforts of building a software system by reusing the components, "component dependency and component interaction" [10].…”
Section: A Methods Used For Improvement In Software Reliability and mentioning
confidence: 99%
“…Furthermore, it shows that ransomware may be identified using individual or shared patterns. Furthermore, Kok et al [14] proposed a pre-encryption algorithm that composed of two phases the first, is a machine learning algorithm used to detect the ransomware before encrypting user files, which based on API pattern recognition. Hence, it uses Cuckoo sandbox to captures the (API) generated by the suspicious program and analyzes them, but it may have a high false positive rate.…”
Section: File Access and File System Activitymentioning
confidence: 99%